Maltase-glucoamylase inhibition potency and cytotoxicity of pyrimidine-fused compounds: An in silico and in vitro approach. (October 2019) - Mehraban, Mohammad Hossein; Mansourian, Mahboubeh; Ahrari, Sajjad; HajiEbrahimi, Ali; Odooli, Salman; Motovali-Bashi, Majid; Yousefi, Reza; Ghasemi, Younes
Graphical abstract: Highlights: Pyrimidine-fused heterocycles proved to interact with crucial amino acids in the active site of human maltase-glucoamylase. The nature of interactions was proved to be hydrophobic and hydrogen bonding. Introducing an additional pyrimidine to the scaffold proved to improve the interaction with this human alpha glucosidase. No significant cytotoxicity was induced by pyrimidine fused heterocycles. Abstract: The prevalence of diabetes mellitus has been incremented in the current century and the need for novel therapeutic compounds to treat this disease has been significantly increased. One of the most promising approaches is to inhibit intestinal alpha glucosidases. Based on our previous studies, four pyrimidine-fused heterocycles (PFH) were selected as they revealed satisfactory inhibitory action against mammalian α-glucosidase. The interaction of these compounds with both active domains of human maltase-glucoamylase (MGAM) and their effect on human Caco-2 cell line were investigated. The docking assessments suggested that binding properties of these ligands were almost similar to that of acarbose by establishing hydrogen bonds especially with Tyr1251 and Arg526 in both C-terminal and N-terminal MGAM, respectively. Also, these compounds indicated a stronger affinity for C-terminal of MGAM.L2 andL4 made tightly complexes with both terminals of MGAM which in turn revealed the importance of introducing pyrimidine scaffold and its hinge compartment. The results of molecular dynamics simulation analyses confirmed the docking data and showed deep penetration ofL2 andL4 into the active site of MGAM. Based on cell cytotoxicity assessments, no significant cell death induction was observed. Hence, these functional MGAM inhibitors might be considered as new potential therapeutic compounds in treatment of diabetes and its complications.